Методи прогнозної оцінки сприятливості геологічного середовища будівництву об'єктів підземної урбаністики - Гайко, Геннадій Іванович; Матвійчук, Іван Олександрович; Білецький, Володимир Стефанович; Салуга, Пьотр (ФОП Петров В. В., 2018)
Стисло окреслено перспективи освоєння підземного простору мегаполісів. Проаналізовано природничо-технічну систему "геоурбаністика – геологічне середовище". Представлено методику типізації геологічного середовища і градацію його сприятливості освоєнню підземного простору. Наведено результати типізації та для ділянки в Шевченківському районі Києва. Візуалізовано тематичні карти для окремих факторів впливу. Розкрито особливості методу морфологічного аналізу для оцінки ризиків розвитку підземної урбаністики, показані його можливості для прогнозної оцінки сприятливості ділянок для геобудівництва. Представлена морфологічна таблиця загальної характеристики та ризиків освоєння підземного простору. Надано аналіз визначених груп факторів. Означено методичні аспекти застосування методу Монте-Карло в геомеханіці. Доведена можливість доповнення поширеного в проектуванні інженерних об’єктів методу скінчених елементів та різних програмних комплексів його реалізації програмним інструментарієм методу Монте-Карло, зокрема в оцінці змінності властивостей геологічного середовища.

The purpose of the paper is to reveal new opportunities and develop tools for applying typing methods, system analysis and probabilistic methods for assessing favorable geological environment of underground urban development. A comprehensive method was used based on methods of geological environment typification, morphological analysis of underground construction sites, Monte Carlo synthesis and finite elements methods, taking into account variability of soil properties in the geocoding area. Scientific results include: a new method of geological environment typification, which examines variability of properties not only of the surface layer in the allocated area, but also the entire thickness of the geological environment for the first time, where the underground object is located; scientific tool for morphological analysis methods to assess the favorable urban conditions for underground construction; synthesis of the Monte Carlo method and the finite element method in order to take into account the probabilistic nature of soils properties when developing the underground space. Practical results: Geological environment on the territories in Shevchenko district of Kyiv was typified; thematic maps for individual factors of influence were created; morphological tables with the analysis of risks for development were constructed, dependencies between the parameters of morphological tables were constructed, specified parameters of underground structures taking into account the probabilistic nature of the properties of the geological environment were calculated. This provides investors and city government administrations with an effective risk management and investment tool for underground urban development.
Forecast assessment methods of geological environment promotion for the construction of urbanistics subjects
Keywords: геоурбаністика; морфологічні таблиці; метод Монте-Карло; георесурси; інженерно-геологічні процеси; управлінські рішення; класифікація техногенних впливів; geological environment; geourbanism; underground space; system approach; forecast estimation; typifying method; morphological analysis; morphological tables; geomechanical risks; Monte Carlo method